Estimation of Carbon Stock in Mangrove Seedling and Sediment in The Muara Gembong Area, Bekasi, West Java - Pahrurrozi Pahrurrozi; Fitra Muazzasari; Eni Suyantri; Neza Okta Sania (Journal of Biology, Environment, and Edu-Tourism, 2025)
Mangrove forests can reduce the amount of carbon in the air by absorbing some of the carbon dioxide through photosynthesis and storing it in the form of biomass and sediment. This study aims to determine the carbon stock of seedlings and sediment in the pond area that has been converted into an ecotourism location. The method of sampling seedlings is done by harvesting, while sediment uses a corer pipe on each transect. Analysis of seedling and sediment research data uses Loss on Ignition (LOI) with different oven volumes. The results of the study showed that carbon stocks were found in plot 1, namely seedlings of 0.34 tons/ha and sediment of 669.95 tons/ha. Meanwhile, the total estimated sediment carbon in all plots was 1.14 tons/ha and sediment of 1,781.68 tons/ha. This study concluded that high seedling carbon stocks were in line with sediment carbon as in plot 1. However, the results of the study showed that sediment stocks were higher than seedlings. Therefore, mangrove-based ecotourism management continues to be improved to maintain and optimize it as a carbon absorber and store.